Hubungan umur, masa kerja dan kuliah online dengan produktifitas dosen pada masa pandemi covid-19 di Universitas “X” kota Semarang. - Supriyono Asfawi; MG Catur Yuantari; Yusthin M Manglapy; Yohanes Pratama; Rini Wulandari Hariono; Wening Wiworo Palupi (Dian Nuswantoro Semarang, 2022)
During the COVID-19 pandemic, the teaching and learning process must continue, work from home is one solution for its implementation. The obligation of lecturers to carry out the Tri Dharma of Higher Education must still be carried out as a benchmark for the success and productivity of lecturers. This study aims to see the level of productivity of lecturers during the covid-19 pandemic at the